Production of activated carbon from palm oil shell waste and its adsorption characteristics - Rahman, Md. Mokhlesur; Nik, Wan Sani; A. M., Yusof; F. N., Ani; C. M, Che Adnan (UTM, 2006)
The effects of raw material treatment and concentration of phosphoric acid on the characteristics of activated carbon were investigated. Adsorptions of Cu, Pb, Cr and Cd in activated carbon were carried out to evaluate the adsorptive capacity of selected activated carbons. It was found that treated raw material reduces inorganic element and increases Brunet Elmer Teller (BET) surface area of the activated carbon. The optimum BET surface area was achieved with following conditions; 30% phosphoric acid concentration, treated raw material, and activation temperature of 500oC with holding time of 2 hours. The optimum BET surface area and the average pore diameter were found to be 1058 m2g-1 and 20.64nm, respectively. The pore size distribution of the activated carbon by scanning electron microscopy (SEM) also confirmed to these conditions. Thermal stability of these samples was investigated using thermal gravimetric analyzer (TGA). The maximum thermal stability was observed up to 6000C. Adsorption studies for activated carbon impregnated with 30% H3PO4 in the application of filter system confirm the adsorbing capacity of activated carbon. In this study, it was observed 100% of Cr was adsorbed followed by Pb (99.8 %), Cd (99.5 %) and Cu (25 %).